Kendala yang Dihadapi Mahasiswa Jurusan Sejarah dalam Menulis Proposal Skripsi - Aisiah Aisiah; Firza Firza (Diakronika, 2018)
Students generally experience obstacles in writing thesis research proposals. The research findings indicate that the problems in writing a thesis proposal by students include; find research ideas, look for literature and empirical data in the field as well as technical constraints related to aspects of writing relating to structure (systematics) and rules for using scientific and standard Indonesian languages. The specific problem of writing proposal research types, among others, relates to the development of a framework that describes the paradigm of relationships between variables, determining the design of experimental designs, how to determine samples and analyze data using formulas and statistics. Constraints on PTK proposal writing, among others, relate to the determination of research design in the form of the PTK cycle including the activities carried out in each cycle, determining indicators of success, data collection and data analysis. While writing a proposal for the type of R & D research students face constraints related to determining product specifications that are attractive and truly needed by teachers and students, relevant literature, writing framework, selection of development models, and product trial designs. The study of this study describes the obstacles faced by students in writing research proposals for history education thesis. The aim is to identify common obstacles experienced by students in writing thesis proposals, including specific obstacles to writing experimental research proposals, CAR and R&D. Data on the constraints of thesis proposal writing are collected by interviewing students, examining their thesis proposals and examining students' written reports about the perceived constraints when writing a thesis proposal. The source of research data comes from students, thesis documents and experience reports writing thesis proposals. This data was analyzed descriptively qualitatively.